Detection and Identification of Human Herpesvirus type 6 (HHV-6) Infection by Polymerase Chain Reactions and Restriction Endonuclease Analysis - Suhartono Suhartono (Biologi Edukasi: Jurnal Ilmiah Pendidikan Biologi, 2009)
Human herpesvirus 6 (HHV-6) is a widespread causative agent of exanthum subitum or roseola infantum. The species of HHV-6 is divided into two variants, HHV-6A and HHV 6-B, which might be detected and identified by PCR and RE methods. The three samples of eye swabs from children with suspected HHV-6 neurological illness were extracted by guanidium isothiocyanate method before running in PCR followed by agarose electrophoresis as a detection stage. The positive results were then identified by RE analysis to determine the variant of the viruses. One of the three samples (sample 2) shows positive result in direct electrophoresis and it was identified as HHV-6B which produced two fragments of 153bp and 70bp in the RE analysis. PCR and RE analysis are useful methods in detection as well as identification of HHV-6